HUBUNGAN SELF EFFICACY DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD N 1 BLANG MANGAT - Parlindungan Siregar; Susi Yusriyanti; Zainal Abidin (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to determine the relationship between self efficacy and mathematics learning outcomes of fifth-grade students at SD Negeri 1 Blang Mangat. The study employed a quantitative approach with a correlational research design. The population consisted of 58 fifth-grade students, all of whom were selected as the research sample using the total sampling technique. Self efficacy data were collected through a questionnaire developed using a five-point Likert scale, while mathematics learning outcome data were obtained from students’ academic records. Data analysis techniques included descriptive analysis, normality testing, and Pearson Product Moment correlation analysis. The results revealed a positive and significant relationship between self efficacy and mathematics learning outcomes. This finding indicates that students with higher levels of self efficacy tend to achieve better mathematics learning outcomes. Conversely, students with lower self efficacy generally obtain lower academic achievement in mathematics. Therefore, self efficacy is considered an important factor influencing students’ mathematics learning outcomes and academic success.